A319 THE MURINE CECAL DEVELOPMENTAL MICRORNA SIGNATURE. (1st March 2018) - Alraefaei, A; Taibi, A; Comelli, E
Abstract: Background: MicroRNAs (miRNAs) play a key role in intestinal gene expression regulation and their dysregulation has been observed in paediatric intestinal pathologies such as necrotizing enterocolitis and inflammatory bowel disease. In this context, miRNAs are being considered as diagnostic and prognostic markers. Though, little is known about the intestinal miRNA signature during postnatal maturation. Aims: To investigate the murine cecal miRNA signature during postnatal maturation Methods: Specific-pathogen-free C57BL/6-Elite male and female mice 6–8 weeks old were housed in sterile conditions. Mice were bred harem-style; at weaning (postnatal day (PND) 21), offspring were caged based on sex and dam. Each litter ( n =7) was followed longitudinally and offspring were sacrificed at PND 14, 21 and 36 ( n =1 male per litter and time point). Total RNA was extracted from cecal tissue and used to profile the expression of 578 miRNAs with the nCounter® Mouse V1.5 miRNA Expression Assay (NanoString Technologies, Inc.). Data was analyzed with nSolver™ Analysis Software 3.0 and statistical analysis and hierarchal clustering were completed in R. Target prediction was completed in TargetScan Release 7.1 and miRDB databases. Results: 207 miRNAs were detected in cecal tissue. Of these, 10 miRNAs were significantly differentially expressed over time ( p <0.05, FDR<0.05) in which 4 miRNAs were overexpressed at both PND 21 and 36 compared to PND 14 (2.0–7.7 fold change) and 6 miRNAs were underexpressed (0.2–0.6 fold change). When comparing PND 36 to PND 21, 2 miRNAs were overexpressed (1.9–16.7 fold change) and 5 miRNAs were underexpressed (0.3–0.6 fold change). Samples clustered according to postnatal age based on the expression profile of these 10 miRNAs. Prediction analysis identified 3, 525 genes as potential targets of these miRNAs, including genes involved in the intestinal barrier function and immune system. Conclusions: This study shows that the cecal miRNA signature evolves during early postnatal life with potential implications for intestinal homeostasis. Selected miRNAs may serve as nutritional or pharmacological targets. Funding Agencies: NSERC Discovery grant to EMC. AA is the recipient of a full scholarship from Kuwait University, State of Kuwait. EMC holds the Lawson Family Chair in Microbiome Nutrition Research at the University of Toronto.